2012
DOI: 10.1088/1475-7516/2012/04/021
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational collapse inf(R) theories

Abstract: We study the gravitational collapse in modified gravitational theories. In particular, we analyze a general f (R) model with uniformly collapsing cloud of self-gravitating dust particles. This analysis shares analogies with the formation of large-scale structures in the early Universe and with the formation of stars in a molecular cloud experiencing gravitational collapse. In the same way, this investigation can be used as a first approximation to the modification that stellar objects can suffer in these modif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
112
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(118 citation statements)
references
References 96 publications
4
112
0
1
Order By: Relevance
“…Starobinsky [15] suggested that quadratic Ricci scalar corrections, i.e., f (R) = R + αR 2 in the field equations could be helpful to cause exponential early universe expansion. Several relativisticts [46] adopted this formulation not only for an inflationary constitute but also as a substitute for dark matter (DM) for α = [48]. This is the minimum value of M which follows from Cavendish-type laboratory tests of the Newton law of gravity.…”
Section: Modified Scalar Variables and F (R T ) Gravitymentioning
confidence: 99%
“…Starobinsky [15] suggested that quadratic Ricci scalar corrections, i.e., f (R) = R + αR 2 in the field equations could be helpful to cause exponential early universe expansion. Several relativisticts [46] adopted this formulation not only for an inflationary constitute but also as a substitute for dark matter (DM) for α = [48]. This is the minimum value of M which follows from Cavendish-type laboratory tests of the Newton law of gravity.…”
Section: Modified Scalar Variables and F (R T ) Gravitymentioning
confidence: 99%
“…Spherically symmetric perfect fluid gravitational collapse has been discussed in metric f (R) gravity by Sharif and Kausar [39]. Cembranos et al [40] analyzed a general f (R) model with uniformly collapsing cloud of self-gravitating dust particles.…”
Section: Introductionmentioning
confidence: 99%
“…Cembranos et al [64] examined GC of non-static inhomogeneous gravitational sources and studied the large-scale structure formation for an early-time cosmos in different f (R) gravity theories. Modified gravity theories are likely to host massive celestial objects with smaller radii as compared to GR [65][66][67][68][69][70].…”
Section: Introductionmentioning
confidence: 99%